Moderating Role of Dividend Policy on the Nexus Between AIL, NPL, and Stock Returns in the Indonesian Financial Sector - Wahyu Nisa’ul Kharimah; Yuliati Yuliati (Journal of Enterprise and Development (JED), 2026)
Purpose: This study examines the influence of Allowance for Impairment Losses (AIL), profitability, and Non-Performing Loans (NPL) on stock returns, with dividend policy serving as a moderating variable, in the Indonesian financial sector following the implementation of PSAK 71.Method: This quantitative research utilizes panel data regression, analyzing data from the financial sector firms listed on the Indonesia Stock Exchange for the period 2020–2024, resulting in 115 data points. Secondary data were obtained from annual reports and financial statements. Model selection, based on the Chow, Hausman, and LM tests, revealed that the fixed effects model was the most suitable. Moderated Regression Analysis (MRA) was applied to assess the moderating role of dividend policy.Result: The findings indicate that AIL significantly influences stock returns, suggesting that investors take credit risk provisioning under the expected credit loss model. In contrast, profitability and NPL do not have a significant effect on stock returns. Additionally, dividend policy moderates the relationship between AIL and stock returns, but does not affect the relationship between profitability or NPL and stock returns.Practical Implications for Economic Growth and Development: These results offer insights for managers, regulators, and investors, highlighting that transparent AIL reporting can enhance investor confidence, strengthen financial stability, and promote efficient capital allocation. Furthermore, a deeper understanding of credit risk contributes to the resilience of the financial sector, fostering sustainable economic growth.Originality/Value: This study contributes to the literature by incorporating dividend policy as a moderating variable within the PSAK 71 framework and providing broader evidence from the Indonesian financial sector.